Long-term results after non-operative and operative treatment of radial neck fractures in adults - Keil, Holger (J Orthop Surg Res, 2018)
BACKGROUND: The aim of this study is to determine the functional long-term outcome after non-operative and operative treatment of radial neck fractures in adults. METHODS: Thirty-four consecutive patients with a mean age of 46.4 (18.0 to 63.0) years with a fracture of the radial neck who were treated between 2000 and 2014 were examined regarding the clinical and radiological outcome. Twenty patients were treated non-operatively, and 14 patients underwent surgery. RESULTS: After a mean follow-up of 5.7 (2.0 to 15.7) years, the clinical scores showed good results in both groups. The Disabilities of Arm, Shoulder and Hand score was 16.1 (0 to 71.6) in the non-operative group and 8.8 (0 to 50.8) in the operative group, respectively. The Mayo Elbow Performance Score was 80.0 (30 to 95) in the non-operative group and 82.5 (35 to 95) in the non-operative group, respectively. The initial angle of the radial head towards the shaft (RHSA) was significantly higher in the operative group in the anterior-posterior plane (12.8° [2 to 23] vs. 26.3° [1 to 90], p = 0.015). In the follow-up radiographs, the RHSA was significantly lower in the operative group (15.1° [3 to 30] vs. 10.9° [3 to 18], p = 0.043). Five patients developed 7 complications in the non-operative group, and 7 patients developed 12 complications in the operative group. Revision rates were higher in the operative groups as 1 patient received radial head resection in the non-operative (5%) group while 7 patients in the operative group (50%) needed revision surgery. CONCLUSION: A good functional long-term outcome can be expected after operative and non-operative treatment of radial neck fractures in adults. If needed due to major displacement, open reduction is associated with a higher risk of complications and the need for revision surgery but can achieve similar clinical results. TRIAL REGISTRATION: DRKS DRKS00012836 (retrospectively registered)